State of the art on the photocatalytic applications of graphene based nanostructures: From elimination of hazardous pollutants to disinfection and fuel generation. Issue 2 (April 2020) - Mamba, G.; Gangashe, G.; Moss, L.; Hariganesh, S.; Thakur, S.; Vadivel, S.; Mishra, A.K.; Vilakati, G.D.; Muthuraj, V.; Nkambule, T.T.I.
Graphical abstract: Highlights: GR based photocatalysts have flexible applicability from removal of pollutants to fuel generation. Incorporation of GR materials accelerate the photocatalytic reaction kinetics. Good electronic conductivity of GR materials is key to efficient charge separation and transfer in nanocomposite photocatalysts. Strong interfacial contact between semiconductor and GR material ensures synergy between materials. Magnetic Z-scheme GR based photocatalysts are more attractive due to high activity and easy separation. Abstract: Adequate, clean water and energy are the cornerstones of human existence and global development. However, water scarcity due to climate change and pollution and the depletion of fossil fuels together with their negative impact on the environment, pose a great global threat. Solar assisted-photocatalysis is a promising tool for environmental pollution mitigation and for generating alternative renewable energy. This review provides a one-stop, comprehensive read on the most recent developments in graphene based photocatalysts towards removal of organic (dyes, emerging pollutants), inorganic (heavy metals, oxides of nitrogen), microbial pollutants and fuel generation from carbon dioxide reduction and water splitting. We began by providing a brief overview of the positive attributes of photocatalysis and the use of graphene in photocatalytic nanostructures. This is followed by the investigation of the latest applications of graphene based photocatalyst in water treatment, air purification, disinfection and energy generation. Details on the specific roles of graphene materials during photocatalysis and the underlying mechanisms propelling the different photocatalytic reactions, are outlined. Finally, some remarks in terms of the current research on graphene materials in photocatalysis for environmental pollution abatement and fuel generation and future considerations, concludes the review.